French Colonial Medicine and Pharmacology in Cambodia, Laos and Vietnam, 1802-1954" - Thompson, C Michele (Science Across the European Empires, 1800-1950, 2005)
Keywords: dept.his

When France was King of 'Kartographie' - Petto, Christine Marie (2005)
Keywords: dept.his; faculty_collection; sabbatical_report

From l'état, c'est moi to l'état, c'est l'état: Mapping in early modern France - Petto, C.M. (Cartographica, 2005)
Using the printed works of two French cartographers, Alexis-Hubert Jaillot and Guillaume Delisle, I investigate how the changing interests of the government directed not only the process of map-making but the rhetoric evident in printed maps and atlases. Jaillot, a commercial map publisher flourishing during the second half of the seventeenth century, produced maps that participated in the fabrication of the image of Louis XIV. Maps served this "cult of image" and contributed to a multimedia show to glorify the reign of the Sun King and to support his personal state - l'état, c'est moi. In the eighteenth century, while a rhetoric of image was still present on printed maps, the "cult of image" was dead and mapping appealed to the rise of the impersonal or bureaucratized state - l'état, c'est l'état. Delisle produced maps as instruments of statecraft that aided the state in furthering its domestic and international interests. In particular, printed maps of the Americas served the government's need to acquire greater territorial control. While images were still powerful on New World maps, the French boundary claims, egregious to some, if uncontested could be produced time and again as a true representation and legitimization of territorial control.
4 citations (Crossref) [2023-10-31]
Keywords: Cartography; France; History; Image; Louis XIV; Printed maps; Rhetoric; Scientific authority; dept.his; eighteenth century; historical cartography; mapping method; territorial delimitation

Land makes the man: topography and national character in german school books - Paddock, Troy R. E. (Lived topographies and their mediational forces, 2005)
"This collection explores the various forms of narrative, semiotic, and technological mediation that shape the experience of place. From the East End of London to Navajo lands to Ground Zero, Lived Topographies examines the great effect of language, mass media, surveillance, and other incursions of the contemporary world on topographical experience and description. Gary Backhaus and John Murungi have assembled a wide array of scholars to provide an interdisciplinary approach to this subject, giving this collection a unique perspective on the phenomenology of place."–Jacket.
OCLC: 57557650
Keywords: dept.his

"Foreword," special issue on "New Perspectives on the Transatlanic Slave Trade - Forbes, Robert P.; Davis, David Brion (William & Mary Quarterly, 2005)
Keywords: dept.his; ⛔ No DOI found

Connecticut Connections: African American Sites in Connecticut: A Laboratory for the History of Slavery and Human Rights - Forbes, Robert P. (Connecticut History Review, 2005)
Keywords: dept.his; ⛔ No DOI found

Book Review: William chester jordan. unceasing strife, unending fear: jacques de thérines and the freedom of the church in the age of the last capetians. princeton: princeton university press. 2005. pp. xi, 154. 29.95Reviews of books and FilmsEurope: ancient and medieval - Friedlander, Alan (The American Historical Review, 2005)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/012-142-032-181-731 tex.type: [object Object]
Keywords: book.review; dept.his

Fighting for a living wage - Rondinone, T (Labor History, 2005)
tex.unique-id: ISI:000230961900023
Keywords: dept.his; ⛔ No DOI found

Book Review: The Rise of Aggressive Abolitionism: Addresses to the Slaves. By Stanley Harrold. (Lexington: University Press of Kentucky, 2004. x, 246 pp. 35.00, isbn 0-8131-2290-2.) - Davis, Hugh (The Journal of American History, 2005)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/006-100-301-517-967 tex.type: [object Object]
Keywords: book.review; dept.his

Book Review: Pope John XXII and his Franciscan cardinal. Bertrand de la Tour and the apostolic poverty controversy . By Patrick Nold. (Oxford Historical Monographs.) Pp. xii+212. Oxford: Clarendon Press, 2003. £45. 0 19 926875 4 - Friedlander, Alan (The Journal of Ecclesiastical History, 2005)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/014-827-091-313-911 tex.type: [object Object]
Keywords: book.review; dept.his

Book Review: Constitutional failure: Carl Schmitt in Weimar: Kennedy, Ellen: Durham: Duke University Press, 288 pp., publication date: July 2004 - Paddock, Troy (History: Reviews of New Books, 2005)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/033-549-317-378-200 tex.type: [object Object]
Keywords: book review; book.review; dept.his

Book Review: Inventing the nation: Germany: Berger, Stefan: New York: Oxford University Press, 274 pp., publication date: July 2000 - Paddock, Troy (History: Reviews of New Books, 2005)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/073-500-529-830-477 tex.type: [object Object]
Keywords: book review; book.review; dept.his